2020
DOI: 10.3390/ijerph17093092
|View full text |Cite
|
Sign up to set email alerts
|

Could Environment Affect the Mutation of H1N1 Influenza Virus?

Abstract: H1N1 subtype influenza A viruses are the most common type of influenza A virus to infect humans. The two major outbreaks of the virus in 1918 and 2009 had a great impact both on human health and social development. Though data on their complete genome sequences have recently been obtained, the evolution and mutation of A/H1N1 viruses remain unknown to this day. Among many drivers, the impact of environmental factors on mutation is a novel hypothesis worth studying. Here, a geographically disaggregated method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This study included both metrological parameters and host factors to determine correlation with frequency of mutations. Studies have found significant effects of environmental factors and UV radiation on the frequency of mutation of influenza virus and Newcastle disease virus [ 42 , 43 ]. This study reported strong correlation between average temperature and mutation frequency at ORF1ab-common mutation ( r s = 0.654), rare mutation ( r s = 0.598) and at S- D614G ( r s = 0.611); between maximum temperature and rare mutation at S ( r s = 0.658).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included both metrological parameters and host factors to determine correlation with frequency of mutations. Studies have found significant effects of environmental factors and UV radiation on the frequency of mutation of influenza virus and Newcastle disease virus [ 42 , 43 ]. This study reported strong correlation between average temperature and mutation frequency at ORF1ab-common mutation ( r s = 0.654), rare mutation ( r s = 0.598) and at S- D614G ( r s = 0.611); between maximum temperature and rare mutation at S ( r s = 0.658).…”
Section: Discussionmentioning
confidence: 99%
“…As of 18 August 2020 no other study has described the correlation between metrological parameters/host factors and frequency of mutations in novel coronaviruses. However, for other viruses like influenza and Newcastle disease viruses there are reports of environmental and host factors association with the virus mutations [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flu-A virus seems to change its antigen more frequent than Flu-B virus [24], which may influence the sensitivity to climate variability. In a study investigating the association between environment and social conditions and H1N1 mutation, the author found that temperature was the main factor associated with the mutation of A/H1N1 viruses [25]. However, there is still limited information on the interaction of temperature, evolution of the influenza virus, and human activity on influenza transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral drugs play a critical role in stopping the progression and spread of influenza, especially in children, the elderly, and immunocompromised individuals (Han et al, 2018). However, the development of effective vaccines and drugs is challenged by the emergence of new virus subtypes due to constant mutation and genome segment rearrangements (Lyons and Lauring, 2018;Jiang et al, 2020). At present, the main types of drugs used in the clinical treatment of influenza are NA inhibitors and M2 channel ion blockers (Shen et al, 2015;Yen, 2016;Yin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%